An impact-resistant and flame-retardant CNTs/STF/Kevlar composite with conductive property for safe wearable design. (May 2023) - Liu, Bing; Liu, Quan; Pan, Yucheng; Zhou, Jianyu; Zhang, Junshuo; Liu, Shuai; Fan, Ziyang; Deng, Huaxia; Hu, Yuan; Gong, Xinglong
Highlights: The nonflammable shear thickening fluid was prepared by using mesoporous silica. The detecting property was endowed by introducing carbon nanotubes to shear thickening suspension. The influence of STF concentration on energy absorption properties of CNTs/STF/Kevlar composites was investigated. The flammability of neat Kevlar and CNTs/STF/Kevlar composite was studied at different oxygen concentrations. Abstract: An intelligent material with shear thickening, flame-retardant and sensing properties was prepared by introducing mesoporous silica and carbon nanotubes to ionic liquids. By impregnating the conductive shear thickening fluid (STF) on Kevlar fabric and drying in an oven, CNTs/STF/Kevlar composite was obtained. Due to the rate-sensitive performance of STF, the yarn pull-out force of CNTs/STF/Kevlar increased 3–4 times compared with that of neat Kevlar, once the impregnation weight gain is 55 wt%. Furthermore, the CNTs/STF/Kevlar composite can maintain intact at 110 m/s incident velocity of bullet, whereas neat Kevlar fabric was penetrated at the same velocity, and exhibited the flame resistance as well due to the thermal insulation property of mesoporous silica and flame-retardant performance of ionic liquids. Then, CNTs/STF/Kevlar composite also performed obvious sensing characteristic due to the introducing of carbon nanotubes, and showed the application potential in the field of safe wearable equipment.